KETIMPANGAN PEMBANGUNAN DI PULAU SULAWESI - Muhammadinah Muhammadinah (Universitas Pasundan, 2023)
Inequality in development arises as a result of demographic differences between regions and is added to the fact that it is not balanced with the principles of justice and equity. The purpose of this study is to see the effect of HDI and poverty levels on development inequality in Sulawesi Island. The population of all provinces on Sulawesi Island is 6 Provinces where all were taken as samples with a 12-year study period from 2011 – 2022. The analytical method uses multiple linear regression with hypothesis testing, namely the t-test and F-test. The results obtained partially HDI has an influence on development inequality, while poverty has no effect on development inequality. But simultaneously the HDI and the poverty rate have an influence on development inequality.